2020
DOI: 10.1108/jima-05-2020-0122
|View full text |Cite
|
Sign up to set email alerts
|

Halal food purchase intention of Muslim students in Spain: testing the moderating effect of need-for-cognition

Abstract: Purpose This paper aims to investigate the purchase intention of halal food products in Spain, from the perspective of Muslim students. Design/methodology/approach Data were collected from 500 Muslim students living in Spain. Variance-based structural equation modelling was applied to evaluate the association between halal credence, attitude towards halal, need for cognition and purchase intention. Findings This study reveals that the need for cognition does not act as a moderating variable, while halal cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 37 publications
0
22
1
6
Order By: Relevance
“…When consumers refer to halal food, they must adhere to certain Islamic criteria and the entire production process, which includes cutting, storing, preparing, and sanitation. According to halal guidelines, businesses must handle animals in a very clean and pure religious manner (Ali et al, 2020;Pradana et al, 2020). Halal-certified products, community knowledge of halal, and demand for value-oriented products and services have all increased in recent years.…”
Section: Resultsmentioning
confidence: 99%
“…When consumers refer to halal food, they must adhere to certain Islamic criteria and the entire production process, which includes cutting, storing, preparing, and sanitation. According to halal guidelines, businesses must handle animals in a very clean and pure religious manner (Ali et al, 2020;Pradana et al, 2020). Halal-certified products, community knowledge of halal, and demand for value-oriented products and services have all increased in recent years.…”
Section: Resultsmentioning
confidence: 99%
“…Research at the end of the path became more diversified. For instance, Pradana, et al (2020) explored the purchase intention of HF in Spain amongst Muslim students and found that the halal credence factor constituted a critical determinant influencing attitude towards halal and purchase intention. Moreover, Ali, et al (2020a) realised that the halal brand image has an important and positive impact on the halal brand perceived quality, satisfaction, trust, and loyalty.…”
Section: The Location Main Pathsmentioning
confidence: 99%
“…In addition to increasing sales and achieving the target, the discount can help stores/brands save store costs, especially if using certain payment methods (Moeliono et al, 2020). Credit or debit cards, for example, customers and stores will incur additional fees, which means the store will lose money compared to cash transactions (Pradana et al, 2022). By offering discounts with cash payments to customers instead of credit or debit, stores help customers, and their own businesses save extra costs.…”
Section: Literature Review Discount Appealmentioning
confidence: 99%